KEDUDUKAN SIGHAT TAQLIQ TALAQ DALAM HUKUM ISLAM - Muhja, Zainal Abidin (JURNAL AKTA YUDISIA, 2019)
Weddings are performed by bond of trust , means that men and women who were married in the territory of the Republic of Indonesia shall have the religion together . The principle of the law of marriage is absolute means to not have a period of time dalaluarsa . Marriage must also be registered at the Office of Religious Affairs and registered atNote Civil . Marriage is an agreement between a man and a woman in the scope of family law . Marriage is a worship that will continue to take place up in heaven . By because it's every couple must keep the rope marriage that is not interrupted and canceled . Inamong those who cancel the marriage are divorce. Divorces according to Language is decided bond . As for the term fiqhi is decided bond of marriage with the pronouncement of talaq or that convey the same to the pronouncement of divorce . This study discusses "the effect of the Sighat Tak'lik agreement on the marriage bond in Sharia and its impact on divorce in religious courts in Tarakan City "The research is aimed to know the result of treaty sighat Tak'lik and its impact on the divorce that happened in court Religion Tarakan City and knowing Forms agreement sighat Tak'lik who cancels wedding in sharia . The type of research that is used is the study of law Juridical Normative among others case approach, conceptual approach and statute approach. Case approach is? the approach by way of doing research on the case - a case that relates to the issues that face .???????????? Keywords: Sighat Taqliq , Talaq, Marriage , Marriage , Shariah